Rethinking the origin of microblade technology: A chronological and ecological perspective. (2nd May 2016) - Yi, Mingjie; Gao, Xing; Li, Feng; Chen, Fuyou
Abstract: There are four hypotheses on the origin of microblade technology in North China: i) that it originated from Siberia before the Last Glacial Maximum; ii) that it emerged in Siberia after the Last Glacial Maximum; iii) that it developed from the long-narrow flakes produced by the long-established knapping tradition in North China; and iv) that it had multi-regional origins, among which, a microblade industry may have emerged from the bipolar technology in northern China. Based on archaeological data from Siberia, Mongolia, the Japanese archipelago, Korean Peninsula, and North China, it is reasonable to say that the technological groundwork of Siberia was more substantial, and the initial microblade technology appeared in Siberia earlier than in the other areas. Microblade technology was involved in core preparation, systematic knapping, soft hammer and indirect/pressure flaking techniques, which were all present in the blade technology in Siberia but hardly ever evidenced in the traditional flaking technology systems in North China. It is well accepted that the microblade technology was closely related the high mobility of foragers to live in harsh environments. The climatic fluctuations of the last glacial in Siberia were more severe than in low latitudes, and placed greater subsistence pressure on hunter–gatherers in Siberia. The advantages of the initial microblade technology in dealing with these hostile circumstances encouraged foragers to employ and develop it, and finally generated its widespread use during the Upper Paleolithic through human migration and cultural transmission in Northeast Asia and North America.